1998
DOI: 10.1292/jvms.60.705
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Effects of Aging on Rat Somatotroph Cells. An Immunohistochemical and Ultrastructural Study.

Abstract: Aging produces alterations in certain functions of the hypothalamo-pituitary axis that result in sexually dimorphic changes in the somatotrophs. Since quantitative morphological data on these age-associated alterations are scarce, we prompted to make a morphometric immunohistochemical assessment as well as undertake an ultrastructural study of the somatotrophic (GH) cell population in male and female rats of different ages. Young (3-month-old), old (20-month-old), and senescent (29-month-old) Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
2
7
2
Order By: Relevance
“…Despite our being able to demonstrate that in the rat pituitary, aging affects not only the different types of hormone-secreting cells but also the FS cells, marked ultrastructural changes in this population similar to those described for some endocrine cells in rats [Có nsole et al, 1998;Jurado et al, 1998] were not depicted in the present study; only moderate, although frequent modifications appeared.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Despite our being able to demonstrate that in the rat pituitary, aging affects not only the different types of hormone-secreting cells but also the FS cells, marked ultrastructural changes in this population similar to those described for some endocrine cells in rats [Có nsole et al, 1998;Jurado et al, 1998] were not depicted in the present study; only moderate, although frequent modifications appeared.…”
Section: Discussioncontrasting
confidence: 85%
“…5). The remarkable changes appearing with age in the different types of endocrine cells that we described previously [Có nsole et al, 1998;Jurado et al, 1998] were also observed here ( fig. 3).…”
Section: Ultrastructural Studiessupporting
confidence: 89%
See 3 more Smart Citations